STRUCTURAL BEHAVIOUR OF REINFORCED CONCRETE (RC) SLABS WITH OPENING STRENGTHENED USING CARBON FIBRE REINFORCED POLYMER (CFRP) - Shahrul Aman, Syafiqah (Universiti Teknologi PETRONAS, 2018)
Concrete slabs with opening are usually designed with the help of traditional rules of thumb proposed by building codes. Such methods however introduced limitations concerning size of opening and the location of applied loads. Furthermore, there is a lack of sufficient information about the load carrying capacity of slab with opening. It is also difficult to model the complex behaviour of RC structures analytically in its non-linear zone. This has led engineers to rely on the empirical formulas which are derived from numerous experiments for the design of RC structures. However, the usage of CFRP to strengthen RC structure with cut-out openings is only addressed to a small extent due to a lack of experimental and theoretical investigations on the variations in geometry, materials and loading conditions. It is clear that more studies on the structural behaviour of strengthened slabs are needed, especially the one with openings and using numerous layers of CFRP sheets. This is to obtain a better understanding of the failure mechanism, to verify current design methods used and to develop new efficient strengthening methods.